Inovação ambiental no contexto brasileiro : origens sociohistóricas e contradições do interesse público de representantes do estado (1808-2016) - Santos, Heraldo Bispo dos (2019)
The socio-historical origins, contexts and contradictions of the public interest of representatives of the Brazilian State regarding environmental innovations is the object of study of this research. The objective was to identify and characterize contexts and contradictions found in the different modes of political organization of the Brazilian State, since the transfer of the Portuguese Crown to Brazil to the Republic, regarding the relationship established by the State Institutions between environment, scientific and technological development. In this sense, we analyzed the public interest of representatives of the Brazilian state, rulers and state intellectuals, around environmental innovations, from the institutionalization of science and technology in the national territory. The critical research approach and dialectical method were chosen for research development. The BATEIA - dialectic analysis device was the main instrument used in the collection and analysis of information. The obtained results point to: (1) the centrality of the constant presence of the State in the definition of economic interest of extraction of Brazilian natural resources. It is possible to state that (2) the State Institutions and State Intellectuals, since the arrival of the Portuguese Court in Brazil, have established conflicts of interest regarding science and development, considering the environmental issue and the technologies resulting from it. secondary. (3) The development of science products still remains linked to the field of health sciences (mainly epidemiology). Another relevant factor is that, (4) the interest of public representatives of contemporary Brazilian political power around environmental innovations is characterized by: (a) through party influence in setting the agenda for environmental innovation given by occupying positions and ministerial functions, most notably the MDB [28.5%] and PSDB [14.2%], compared to PT, PCdoB and PSD [4.1%]; (b) the concentration on the south-southeast axis of the country [85.7%] in the distribution of regional representativeness of origin of the occupants of the positions of Minister of Science, Technology, Innovations and Communications (MCTIC); (c) the maintenance of careers related to the State Institution, with emphasis on the career of politician [30%], engineer and lawyer [14%], respectively, regarding the occupational profile of MCTIC occupants. Finally, we identified the fragile structuring of environmental innovation management systems in Brazil. (5) The elements that make it difficult to structure Brazilian environmental innovation management systems are influenced by the late institutionalization of science in the country, including: (a) the lack of prestige of the international pressure of environmental regulation on productive, industrial processes and technological in the Brazilian domestic economy; (b) maintenance of disjointed actions of research and development activities in the environment and innovation; (c) low levels of governance; (d) lack of conditions and transparency for the establishment of transnational corporations in the national territory; (e) absence of incentive for exclusive research on environmental innovations in Brazil. It is recommended to analyze the short- and medium-term effects of the results obtained in this research for the management of structured environmental innovation systems.